THE ANALYSIS STUDY OF INTERVENTIONS FOR DRY EYES: A COMPREHENSIVE SYSTEMATIC REVIEW - Rosalina Tamzil, Putri; Diantinia,; Anten, Ratna (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Dry eye disease (DED) results from dysregulated ocular inflammation, causing persistent ocular surface dysfunction, with a global surge in prevalence, especially among children and adolescents, due to increased technology use. Beyond significant ocular morbidity, DED's association with systemic autoimmune disorders, impact on quality of life, and links to psychological and sleep disorders underscore its extensive repercussions. This systematic review aims to comprehensively explore an integrated approach to managing DED, emphasizing preventive and promotive strategies across various levels of healthcare. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: This systematic review investigated final 15 articles. After looking at the titles and summaries, we found 6 papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included four papers in our final analysis. These papers included a retrospective observational study, prospective study, and double-blind, randomized, placebo-controlled trial, and prospective interventional pilot study. Conclusion: In summary, a study suggests that OPT-IPL (Optilight Intense Pulse Light) treatment enhances tear film lipid layer (TFLL) and improves signs and symptoms of dry eye disease (DED) by enhancing meibomian gland function. The phase 3 trial with NOV03 provides compelling evidence of reduced DED signs and symptoms over 8 weeks, demonstrating statistical and clinical significance, with good tolerability. Additionally, the ESSENCE-2 trial highlights the efficacy of a water-free cyclosporine solution in improving ocular surface staining associated with DED, showcasing potential advantages over existing therapies. Our study revealed promising and safe outcomes for dietary supplementation, which preserved tear production in a rat dry eye model and showed significant improvements in both objective parameters and subjective dry eye symptoms. However, further data is needed to validate its widespread use as a common intervention.